Identifying Moderators in the Link Between Workplace Discrimination and Health/Well-Being - Xu, Yue Ethel; Chopik, William J. (Frontiers in Psychology, 2020)
The stress that arises from workplace discrimination can have a large impact on an employee’s work attitude, their work and life satisfaction, and oftentimes whether or not they stay in a job. Workplace discrimination can also have a considerable influence on employees’ short- and long-term health. However, less is known about the factors that might mitigate or exacerbate the effects of discrimination on health. The current study focused not only on the links between workplace discrimination and health, and but also on the effects of potential moderators of the discrimination-health link (i.e., perceived control, Big Five personality traits, optimism, and coworker/supervisor support). People with high neuroticism, high extraversion and high agreeableness were more negatively affected by workplace discrimination than those low on neuroticism, extraversion, and agreeableness. Perceived control was found to be a protective factor, such that those high in perceived control had fewer chronic illnesses in the context of high levels of workplace discrimination.